On Crossed Modules and Crossed Homomonphisms - Abdul Mohammed; Manal Abd Fathi (Al-Rafidain Journal of Computer Sciences and Mathematics)
The purpose of this paper is to study the crossed modules and crossed homomonphisms, and since these concepts are related to the group actions on groups we presented these types of actions.